Functional Characterization of a L-2-Haloacid Dehalogenase From Zobellia galactanivorans DsijT Suggests a Role in Haloacetic Acid Catabolism and a Wide Distribution in Marine Environments - Grigorian, Eugénie; Groisillier, Agnès; Thomas, François; Leblanc, Catherine; Delage, Ludovic (Frontiers in Microbiology, 2021)
L-2-halocid dehalogenases (L-2-HADs) have been mainly characterized from terrestrial polluted environments. By contrast, knowledge is still scarce about their role in detoxification of predominant halocarbons in marine environments. Here, phylogenetic analyses showed a wide diversity of homologous L-2-HADs, especially among those belonging to marine bacteria. Previously characterized terrestrial L-2-HADs were part of a monophyletic group (named group A) including proteins of terrestrial and marine origin. Another branch (named group B) contained mostly marine L-2-HADs, with two distinct clades of Bacteroidetes homologs, closely linked to Proteobacteria ones. This study further focused on the characterization of the only L-2-HAD from the flavobacterium Zobellia galactanivorans DsijT (ZgHAD), belonging to one of these Group B clades. The recombinant ZgHAD converted bromo- and iodoacetic acids into glycolate, and gene knockout in Z. galactanivorans revealed a direct role of ZgHAD in tolerance against both haloacetic acids. Analyses of metagenomic and metatranscriptomic datasets confirmed that L-2-HADs from group A were well-represented in terrestrial and marine bacteria, whereas ZgHAD homologs (group B L-2-HADs) were mainly present in marine bacteria, and particularly in host-associated species. Our results suggest that ZgHAD homologs could be key enzymes for marine Bacteroidetes, by conferring selective advantage for the recycling of toxic halogen compounds produced in particular marine habitats, and especially during interactions with macroalgae.